Composition for forming a barrier material, barrier material and its manufacturing method, and product and its manufacturing method

JP7642984B2Active Publication Date: 2025-03-11RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020079414
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-07
Filing Date
2020-04-28
Publication Date
2025-03-11
Estimated Expiration
2040-04-28

AI Technical Summary

Benefits of technology

【0030】 本発明は、様々な形状の対象物に適用可能な、防湿性に優れるバリア材を提供できる。本発明はまた、上記バリア材を形成するための、バリア材形成用組成物を提供できる。本発明は更に、上記バリア材の製造方法、上記バリア材を備える製品、及び当該製品の製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642984000001
    Figure 0007642984000001
  • Figure 0007642984000002
    Figure 0007642984000002
  • Figure 0007642984000003
    Figure 0007642984000003
Patent Text Reader

Abstract

To provide a barrier material that can be applied to objects of various shapes and has excellent moisture proofness.SOLUTION: A barrier material forming composition has silane oligomers, and linear polysiloxane with a 25°C kinematic viscosity of 50 mm2 / s or more, the silane oligomers being at least partially modified with metalalkoxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for forming a barrier material, a barrier material and a method for producing the same, and a product and a method for producing the same. [Background technology]

[0002] Conventionally, in order to prevent moisture from entering gaps formed in electronic components, sealing the electronic components with a barrier film etc. For example, Patent Document 1 describes a barrier film laminate in which barrier films having inorganic oxide layers are laminated. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-093195 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, since the barrier film laminate described in Patent Document 1 is in the form of a film, its applicable targets are limited.

[0005] Therefore, an object of the present invention is to provide a barrier material having excellent moisture resistance and applicable to objects of various shapes. Another object of the present invention is to provide a barrier material-forming composition for forming the barrier material. Another object of the present invention is to provide a method for producing the barrier material, a product including the barrier material, and a method for producing the product. [Means for solving the problem]

[0006] The present invention relates to a silane oligomer and a kinetic viscosity of 50 mm at 25°C. 2and a linear polysiloxane having a molecular weight of at least 1000 s, wherein at least a portion of the silane oligomer is modified with a metal alkoxide.

[0007] By applying such a composition to an object, a barrier material having excellent moisture resistance can be easily formed on the object. In addition, since the composition contains linear polysiloxane, a barrier material having excellent conformability to the object and having few defects such as cracks can be formed.

[0008] In one embodiment, the linear polysiloxane may have a diorganopolysiloxane chain.

[0009] In one embodiment, the linear polysiloxane may have a group selected from the group consisting of a silanol group and an alkoxy group at both ends.

[0010] In one embodiment, the linear polysiloxane has a kinetic viscosity of 500 mm at 25° C. 2 / s or less.

[0011] In one embodiment, the content of the linear polysiloxane may be 1 to 30 parts by mass with respect to 100 parts by mass of the silane oligomer.

[0012] In one embodiment, the silane oligomer may have a silicon atom bonded to three oxygen atoms.

[0013] In one embodiment, the ratio of the total number of silicon atoms bonded to three oxygen atoms and silicon atoms bonded to four oxygen atoms to the total number of silicon atoms in the silane oligomer may be 30% or more.

[0014] The composition according to one embodiment may further comprise a silane monomer.

[0015] In one embodiment, the silane monomer may include a first silane monomer having a reactive functional group selected from the group consisting of a vinyl group, an epoxy group, a glycidyl group, a (meth)acryloyl group, an amino group, an isocyanate group, an isocyanurate group, and a mercapto group, and a second silane monomer selected from the group consisting of an alkyltrialkoxysilane, an aryltrialkoxysilane, and a tetraalkoxysilane.

[0016] In one embodiment, the content of the first silane monomer may be 0.01 to 5 parts by mass with respect to 100 parts by mass of the silane oligomer.

[0017] In one embodiment, the content of the second silane monomer may be 5 to 40 parts by mass based on 100 parts by mass of the silane oligomer.

[0018] In one embodiment, the metal alkoxide may be an aluminum alkoxide.

[0019] The present invention also relates to a method for producing a silane oligomer at least partially modified with a metal alkoxide, and a method for producing a silane oligomer having a kinetic viscosity of 50 mm at 25° C. 2 and a second step of mixing the composition with a linear polysiloxane having a molecular weight of at least 1000 mol / s to obtain the composition for forming a barrier material.

[0020] In one embodiment, the first step may include a step of reacting a silane oligomer with a metal alkoxide to modify at least a portion of the silane oligomer with the metal alkoxide.

[0021] In one embodiment, the first step may include reacting a silane monomer with a metal alkoxide to form a silane oligomer at least partially modified with the metal alkoxide.

[0022] The present invention also provides a method of producing a barrier material, comprising the step of curing the composition to form a barrier material.

[0023] The present invention also provides a method for producing an article having a moisture-proof treated member, which may include a first step of applying the composition onto the member, and a second step of curing the applied composition to form a barrier material on the member.

[0024] The present invention also provides a method for producing a product having a first member and a second member bonded to the first member, the bonded portion between the first member and the second member being moisture-proofed. This method may include a first step of disposing the composition between the first member and the second member, and a second step of curing the composition to form a barrier material and bonding the first member and the second member via the barrier material.

[0025] The present invention also provides a method of manufacturing an article comprising a moisture barrier member, which may include a first step of curing the composition to produce a moisture barrier member having a barrier material, and a second step of assembling a plurality of components comprising the moisture barrier member.

[0026] The present invention also provides a barrier material which is a cured product of the above composition.

[0027] The present invention also provides an article of manufacture comprising a member and the above-described barrier material formed on the member.

[0028] The present invention also provides a product comprising a first member, a second member, and the barrier material provided between the first member and the second member, wherein the first member and the second member may be bonded to each other via the barrier material.

[0029] The present invention further provides an article of manufacture which is an assembly of multiple components including a moisture barrier component having the above-described barrier material. Effect of the Invention

[0030] The present invention can provide a barrier material having excellent moisture resistance and applicable to objects of various shapes. The present invention can also provide a barrier material-forming composition for forming the barrier material. The present invention can further provide a method for producing the barrier material, a product including the barrier material, and a method for producing the product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] A preferred embodiment of the present invention will be described below. In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this embodiment may be used alone or in combination of two or more.

[0032] <Barrier material forming composition> The barrier material forming composition according to the present embodiment is a composition comprising a silane oligomer and a kinetic viscosity of 50 mm at 25° C. 2 and at least one linear polysiloxane having a molecular weight of at least 1000 silane oligomers, at least a portion of which is modified with a metal alkoxide.

[0033] By applying such a composition to an object, a barrier material having excellent moisture resistance can be easily formed on the object. In addition, since the composition contains linear polysiloxane, a barrier material having excellent conformability to the object and having few defects such as cracks can be formed.

[0034] The barrier material-forming composition may be in a liquid or paste form, and is preferably in a liquid form from the viewpoint of easier application to an object.

[0035] A silane oligomer is a polymer of a silane monomer, and has a structure in which a plurality of silicon atoms are linked via oxygen atoms. In this specification, the silane oligomer refers to a polymer having a molecular weight of 100,000 or less.

[0036] In this specification, a silane oligomer modified with a metal alkoxide is a compound formed by the reaction of a silane oligomer with a metal alkoxide, and can also be said to be a compound having a structure in which a silicon atom derived from the silane oligomer and a metal atom derived from the metal alkoxide are bonded via an oxygen atom.

[0037] The silane oligomer modified with a metal alkoxide (hereinafter sometimes referred to as "modified silane oligomer") may be a reaction product of a silane oligomer and a metal alkoxide, or a reaction product of a silane monomer and a metal alkoxide. In the latter case, the silane monomer reacted with the metal alkoxide may further react with another silane monomer to form a silane oligomer structure, or the silane oligomer formed by the reaction between silane monomers may be reacted with a metal alkoxide.

[0038] In the composition according to the present embodiment, it is not necessary that all of the silane oligomer contained in the composition is modified with a metal alkoxide, but it is sufficient that at least a portion of the silane oligomer is modified with a metal alkoxide.

[0039] The silicon atoms contained in the silane oligomer can be classified into silicon atoms bonded to one oxygen atom (M unit), silicon atoms bonded to two oxygen atoms (D unit), silicon atoms bonded to three oxygen atoms (T unit), and silicon atoms bonded to four oxygen atoms (Q unit). The M unit, D unit, T unit, and Q unit can be exemplified by the following formulae (M), (D), (T), and (Q), respectively.

[0040] [ka]

[0041] In the above formula, R represents an atom (such as a hydrogen atom) or an atomic group (such as an alkyl group) other than an oxygen atom bonded to silicon. Information on the content of these units can be obtained by Si-NMR.

[0042] In the silane oligomer, the ratio of the total number of T units and Q units to the total number of silicon atoms may be, for example, 30% or more, preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, or even 100%. By using such a silane oligomer, a barrier material with even more excellent moisture resistance can be obtained.

[0043] In a preferred embodiment, the silane oligomer preferably contains T units. The content of T units in the silane oligomer is, for example, 10% or more, preferably 20% or more, 30% or more, 40% or more, 50% or more, 70% or more, 80% or more, or 90% or more, or may be 100%, based on the total number of silicon atoms. Such a silane oligomer tends to have improved flexibility.

[0044] In another preferred embodiment, the content of Q units in the silane oligomer is, for example, 50% or more, preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more, based on the total number of silicon atoms, and may be 100%. Such a silane oligomer tends to have further improved moisture resistance and transparency.

[0045] The silane oligomer preferably has an alkyl group or an aryl group as R in the above formulas (M), (D), (T) and (Q).

[0046] The alkyl group is preferably an alkyl group having 6 or less carbon atoms, more preferably an alkyl group having 4 or less carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, and a butyl group, and among these, a methyl group, an ethoxy group, and a propyl group are preferred, and a methyl group is more preferred.

[0047] Examples of the aryl group include a phenyl group, a substituted phenyl group, etc. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, a cyano group, etc. The aryl group is preferably a phenyl group.

[0048] The weight average molecular weight of the silane oligomer may be, for example, 400 or more, preferably 600 or more, more preferably 1000 or more. The weight average molecular weight of the silane oligomer may be, for example, 30000 or less, preferably 10000 or less, more preferably 6000 or less. When the weight average molecular weight of the silane oligomer is large, the flexibility tends to be improved, and when it is small, the moisture resistance and transparency tend to be improved. In this specification, the weight average molecular weight of the silane oligomer indicates the value of the weight average molecular weight expressed in terms of polystyrene measured by gel permeation chromatography (GPC).

[0049] The metal alkoxide is, for example, M(OR 1 ) n M represents a metal atom with a valence of n, and R 1 represents an alkyl group, and n represents a positive number of 1 or more.

[0050] n is preferably 2 to 5, and more preferably 3 to 4.

[0051] Examples of M include aluminum, titanium, zirconium, and niobium, among which aluminum, titanium, and zirconium are preferred, and aluminum is more preferred. That is, examples of metal alkoxides include aluminum alkoxides, titanium alkoxides, zirconium alkoxides, and niobium alkoxides, among which aluminum alkoxides, titanium alkoxides, and zirconium alkoxides are preferred, and aluminum alkoxides are more preferred.

[0052] R 1 R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 2 to 4 carbon atoms. 1 Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, and a butyl group. Of these, an ethyl group, a propyl group, and a butyl group are preferred, and a propyl group and a butyl group are more preferred.

[0053] The composition according to the present embodiment may contain a modified silane oligomer obtained by modifying a silane oligomer with 0.001 to 30 parts by mass of a metal alkoxide relative to 100 parts by mass of the silane oligomer. The amount of the metal alkoxide is preferably 0.02 parts by mass or more, more preferably 0.05 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the silane oligomer. When the amount of the metal alkoxide is large, the curability tends to be better, and when the amount of the metal alkoxide is small, the transparency tends to be improved.

[0054] The linear polysiloxane can be said to be a compound having a linear main chain formed by siloxane bonds, and the main chain is preferably a diorganopolysiloxane chain. That is, the linear polysiloxane preferably has a polysiloxane chain composed of repeating D units.

[0055] The organic group bonded to the silicon atom in the main chain of the linear polysiloxane (that is, R in formula (D)) is preferably an alkyl group or an aryl group.

[0056] The alkyl group is preferably an alkyl group having 6 or less carbon atoms, more preferably an alkyl group having 4 or less carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, and a butyl group, and among these, a methyl group, an ethoxy group, and a propyl group are preferred, and a methyl group is more preferred.

[0057] Examples of the aryl group include a phenyl group, a substituted phenyl group, etc. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, a cyano group, etc. The aryl group is preferably a phenyl group.

[0058] The linear polysiloxane preferably has a group selected from the group consisting of a silanol group and an alkoxy group at at least one end, more preferably has such groups at both ends, and the silicon atom at the end bonded to the group is preferably a Q unit or a D unit, more preferably a D unit.

[0059] The alkoxy group is preferably an alkoxy group having 6 or less carbon atoms, and more preferably an alkoxy group having 4 or less carbon atoms. Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group, and among these, a methoxy group, an ethoxy group, and a propoxy group are preferred, and a methoxy group and an ethoxy group are more preferred.

[0060] The kinetic viscosity of linear polysiloxane at 25°C is 50mm 2 Since such a linear polysiloxane has a sufficient chain length, the above-mentioned effects due to the incorporation of the linear polysiloxane can be significantly obtained.

[0061] The linear polysiloxane preferably has a kinetic viscosity of 60 mm at 25° C. in order to obtain the above-mentioned effects more significantly. 2 / s or more, and more preferably 70 mm 2 / s or more.

[0062] The kinetic viscosity of linear polysiloxane at 25°C is 500mm 2 / s or less. This makes the linear polysiloxane highly compatible with other components in the composition, and improves the transparency of the barrier material-forming composition and the barrier material that is the cured product thereof. From the viewpoint of obtaining this effect more significantly, the kinetic viscosity of the linear polysiloxane at 25°C is preferably 300 mm 2 / s or less is more preferable, and 100 mm 2 It is more preferable that the ratio is 1 / s or less.

[0063] The content of the linear polysiloxane may be, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the silane oligomer. This makes the above-mentioned effects more pronounced. The content of the linear polysiloxane may be, for example, 40 parts by mass or less, preferably 30 parts by mass or more, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the silane oligomer. This makes the coating film more dense and tends to have particularly excellent moisture resistance.

[0064] In this specification, "100 parts by mass of silane oligomer" does not include the mass of the metal alkoxide that modifies the silane oligomer, and means that the total amount of the silane oligomer portion of the modified silane oligomer and the unmodified silane oligomer is 100 parts by mass.

[0065] The composition according to the present embodiment may further contain a silane monomer. By blending the silane monomer, for example, the content of T units and Q units in the barrier material can be adjusted, and the barrier material can be given effects such as transparency and flexibility depending on the application. In addition, by blending the silane monomer, a barrier material with even better moisture resistance tends to be obtained.

[0066] The composition according to the present embodiment preferably contains, as the silane monomer, at least one of a first silane monomer and a second silane monomer, which will be described later, and more preferably contains both.

[0067] The first silane monomer is a silane monomer having a reactive functional group selected from the group consisting of a vinyl group, an epoxy group, a glycidyl group, a (meth)acryloyl group, an amino group, an isocyanate group, an isocyanurate group, and a mercapto group. When the composition contains such a silane monomer, a barrier material having even better conformability and adhesion to an object is formed.

[0068] Although the reason why the first silane monomer exerts the above-mentioned effect is not necessarily clear, it is believed that when the barrier material is formed, a crosslinked structure other than a siloxane bond is formed by a reaction between reactive functional groups, a reaction between a reactive functional group and a silanol group, etc., thereby realizing excellent moisture resistance and flexibility. It is also believed that when the barrier material is formed, the reactive functional group of the first silane monomer bonds with a functional group present on the surface of the object, thereby realizing even more excellent moisture resistance and flexibility.

[0069] From the viewpoint of further improving the flexibility of the barrier material and the adhesion to a member, the reactive functional group of the first silane monomer is preferably selected from the group consisting of a vinyl group, an epoxy group (more preferably a glycidyl group), a (meth)acryloyl group, an amino group, an isocyanate group, an isocyanurate group and a mercapto group, and an amino group is more preferable.

[0070] The first silane monomer preferably has a silicon atom bonded to three oxygen atoms.

[0071] As the first silane monomer, for example, a silane monomer represented by the following formula (A-1) can be suitably used.

[0072] [ka]

[0073] In the formula, R A1 indicates a reactive functional group, L 1 is an alkanediyl group or an oxyalkanediyl group (-OL 2 -, L 2 represents an alkanediyl group; p represents an integer of 0 or more (preferably an integer of 0 to 3); R A2 represents an alkyl group or an aryl group.

[0074] R A1 When is a vinyl group, p is preferably 0 to 3, and more preferably 0.

[0075] R A1 When p is an epoxy group, a glycidyl group, a (meth)acryloyl group, an amino group, an isocyanate group, an isocyanurate group, or a mercapto group, p is preferably an integer of 1 or more, more preferably 1 to 3, and further preferably 1.

[0076] R A1 is a vinyl group, a glycidyl group, or a (meth)acryloyl group, L 1 is preferably an oxyalkanediyl group.

[0077] R A1 is an amino group, an isocyanate group, an isocyanurate group, or a mercapto group, L 1 is preferably an alkanediyl group.

[0078] L 1 and L 2 The alkanediyl group in the above formula (I) is preferably an alkanediyl group having 2 to 10 carbon atoms, and more preferably an alkanediyl group having 2 to 8 carbon atoms.

[0079] R A2 The alkyl group in is preferably an alkyl group having 6 or less carbon atoms, and more preferably an alkyl group having 4 or less carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group (n-propyl group, isopropyl group), a butyl group (n-butyl group, sec-butyl group, isobutyl group, tert-butyl group), and the like.

[0080] R A2 The aryl group in is preferably a phenyl group.

[0081] R A2 is preferably an alkyl group.

[0082] The content of the first silane monomer may be, for example, 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, based on 100 parts by mass of the silane oligomer. This tends to improve the conformability and adhesion. The content of the first silane monomer may be, for example, 5 parts by mass or less, preferably 4 parts by mass or less, more preferably 2 parts by mass or less. This tends to improve the thermal stability of the cured product.

[0083] In this specification, "100 parts by mass of silane oligomer" does not include the mass of the metal alkoxide that modifies the silane oligomer, and means that the total amount of the silane oligomer portion of the modified silane oligomer and the unmodified silane oligomer is 100 parts by mass.

[0084] The second silane monomer is a silane monomer other than the first silane monomer, for example, selected from the group consisting of alkyltrialkoxysilanes, aryltrialkoxysilanes, and tetraalkoxysilanes.

[0085] By blending the second silane monomer, for example, the contents of T units and Q units in the barrier material can be adjusted, and the barrier material can be provided with effects such as transparency and flexibility depending on the application. In addition, blending the second silane monomer tends to provide a barrier material with even more excellent moisture resistance.

[0086] The content of the second silane monomer is not particularly limited, but may be, for example, 5 parts by mass or more, preferably 8 parts by mass or more, more preferably 10 parts by mass or more, relative to 100 parts by mass of the silane oligomer. This tends to further improve the flexibility of the cured product. The content of the first silane monomer may be, for example, 40 parts by mass or less, preferably 35 parts by mass or less, more preferably 30 parts by mass or less. This tends to reduce the volatility of the coating liquid and further improve workability.

[0087] Alkyltrialkoxysilanes are silane compounds in which one alkyl group and three alkoxy groups are bonded to a silicon atom.

[0088] The alkyl group of the alkyltrialkoxysilane is preferably an alkyl group having 6 or less carbon atoms, more preferably an alkyl group having 4 or less carbon atoms. Specific examples of the alkyl group include methyl, ethyl, propyl, butyl, etc., among which methyl, ethyl, and propyl are preferred, and methyl is more preferred. In addition, the alkoxy group of the alkyltrialkoxysilane is preferably an alkoxy group having 6 or less carbon atoms, more preferably an alkoxy group having 4 or less carbon atoms. Specific examples of the alkoxy group include methoxy, ethoxy, propoxy, butoxy, etc., among which methoxy, ethoxy, and propoxy are preferred, and methoxy and ethoxy are more preferred.

[0089] Aryltrialkoxysilanes are silane compounds in which one aryl group and three alkoxy groups are bonded to a silicon atom.

[0090] Examples of the aryl group of the aryltrialkoxysilane include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. The aryl group is preferably a phenyl group. The alkoxy group of the aryltrialkoxysilane is preferably an alkoxy group having 6 or less carbon atoms, and more preferably an alkoxy group having 4 or less carbon atoms. Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group, and among these, a methoxy group, an ethoxy group, and a propoxy group are preferred, and a methoxy group and an ethoxy group are more preferred.

[0091] Tetraalkoxysilane is a silane compound in which four alkoxy groups are bonded to a silicon atom.

[0092] The alkoxy group of the tetraalkoxysilane is preferably an alkoxy group having 6 or less carbon atoms, and more preferably an alkoxy group having 4 or less carbon atoms. Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group, and of these, a methoxy group, an ethoxy group, and a propoxy group are preferred, and a methoxy group and an ethoxy group are more preferred.

[0093] Specific examples of the second silane monomer include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.

[0094] The composition according to the present embodiment may further comprise a liquid medium. The liquid medium includes water and an organic solvent.

[0095] Examples of the organic solvent include alcohols, ethers, ketones, esters, hydrocarbons, etc. In addition to these, acetonitrile, acetamide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc. can also be used.

[0096] In a preferred embodiment, the composition may contain water and alcohols as a liquid medium. By using such a liquid medium, a barrier material having excellent transparency can be easily obtained.

[0097] The alcohol is preferably one that can be vaporized by heating when forming the barrier material. As the alcohol, for example, alcohols having 6 or less carbon atoms are preferred, and alcohols having 1 to 4 carbon atoms are more preferred.

[0098] As the alcohol, for example, an alcohol corresponding to the alkoxy group of the metal alkoxide may be used. That is, for example, when the metal alkoxide has a tert-butoxy group, tert-butyl alcohol may be used as the alcohol. This tends to further improve transparency.

[0099] The content of the liquid medium is not particularly limited, and may be, for example, a content that provides a viscosity suitable for application of the composition. The viscosity of the composition is not particularly limited, and may be appropriately adjusted depending on the thickness of the barrier material to be prepared, the application method, the shape of the target object, etc.

[0100] The viscosity of the composition at 25° C. may be, for example, from 1 to 6000 mPa s, and preferably from 5 to 3000 mPa s. Such a composition makes it easier to apply to an object and to form a barrier material on the object.

[0101] In the composition according to the present embodiment, the molar ratio (M / Si) of metal atom M derived from metal alkoxide to the total number of silicon atoms derived from silane oligomer, linear polysiloxane and silane monomer may be, for example, 0.00001 or more, and is preferably 0.0001 or more. This tends to improve curability. In addition, the molar ratio (M / Si) may be, for example, 0.5 or less, and is preferably 0.2 or less. This tends to improve transparency.

[0102] The composition according to the present embodiment may further contain a curing catalyst. The curing catalyst is not particularly limited as long as it accelerates the polymerization reaction of the silane oligomer or the like.

[0103] Examples of the curing catalyst include acid catalysts including hydrochloric acid, nitric acid, sulfuric acid, acetic acid, phosphoric acid, etc.; metal catalysts including tin, titanium, aluminum, zinc, iron, cobalt, manganese, etc.; and base catalysts including aliphatic amines, ammonium hydroxide, tetraethylammonium hydroxide, sodium carbonate, sodium hydroxide, etc.

[0104] The content of the curing catalyst may be, for example, 0.02 parts by mass or more, preferably 0.05 parts by mass or more, and may be 20 parts by mass or less, preferably 10 parts by mass or less, relative to 100 parts by mass of the silane oligomer.

[0105] The composition according to the present embodiment may further contain other components in addition to those described above. Examples of the other components include resins having hydroxyl groups in their molecular structure, metal oxide particles, metal oxide fibers, and the like. Examples of resins having hydroxyl groups in their molecular structure include polyvinyl alcohol, and the like. Examples of the metal oxide particles include silica particles, alumina particles, and the like, and these particles are preferably nano-sized (for example, the particle size is 1 nm or more and less than 1000 nm) (i.e., nanosilica particles and nanoalumina particles are preferred). Examples of the metal oxide fibers include alumina fibers, and the fiber diameter of these metal oxide fibers is preferably nano-sized (for example, the fiber diameter is 1 nm or more and less than 1000 nm) (i.e., alumina nanofibers are preferred).

[0106] The content of the other components is not particularly limited as long as the above-mentioned effects are obtained, and may be, for example, 50 parts by mass or less, preferably 40 parts by mass or less, relative to 100 parts by mass of the silane oligomer. The content of the other components may be, for example, 10 parts by mass or more, or 20 parts by mass or more, relative to 100 parts by mass of the silane oligomer.

[0107] The method for producing the composition according to the present embodiment includes the following method. <Method of producing the composition 1> The present production method includes a modification step of reacting a silane oligomer with a metal alkoxide to modify at least a portion of the silane oligomer with the metal alkoxide. In this modification step, the metal alkoxide reacts with the silane oligomer to form a metal atom-oxygen atom-silicon atom bond.

[0108] The reaction may be carried out in a liquid medium. Examples of the liquid medium include the same as those mentioned above. The amount of the liquid medium is not particularly limited, and may be, for example, an amount that allows the concentration of the silane oligomer in the reaction liquid to be 50 to 99% by mass (preferably 80 to 95% by mass).

[0109] The reaction conditions for the above reaction are not particularly limited. For example, the reaction temperature for the above reaction may be 60 to 100° C., or may be 70 to 90° C. The reaction time for the above reaction may be, for example, 0.5 to 5.0 hours, or may be 1.0 to 3.0 hours.

[0110] The present production method may further include a step of adding a silane oligomer to the reaction liquid after the modification step, thereby obtaining a composition containing the silane oligomer modified with the metal alkoxide and the unmodified silane oligomer.

[0111] The present manufacturing method may further include a step of adding a linear polysiloxane (and a silane monomer, if necessary) to the reaction liquid after the modification step. That is, the present manufacturing method may include a first step of preparing a silane oligomer at least partially modified with a metal alkoxide, and a second step of mixing the modified silane oligomer and the linear polysiloxane to obtain a barrier material-forming composition, and the first step may be the modification step. This results in the above-mentioned barrier material-forming composition.

[0112] The present production method may further include a step of adding other components to the reaction solution after the modification step. The present production method may further include a step of adding a liquid medium to the reaction solution after the modification step, or a step of replacing the liquid medium in the reaction solution after the modification step with another liquid medium. By these steps, various aspects of the above-mentioned composition can be prepared from the reaction solution after the modification step.

[0113] <Composition manufacturing method 2> The present manufacturing method includes a modification step of reacting a silane monomer with a metal alkoxide to form a silane oligomer at least partially modified with the metal alkoxide. In the modification step, a silane oligomer may be formed by polymerization of the silane monomer, and the formed silane oligomer may be modified with the metal alkoxide. In addition, in the modification step, after the silane monomer is modified with the metal alkoxide, a silane oligomer portion may be formed by reaction of the modified silane monomer with another silane monomer.

[0114] The reaction may be carried out in a liquid medium. Examples of the liquid medium include the same as those mentioned above. The amount of the liquid medium is not particularly limited, and may be, for example, an amount that allows the concentration of the silane monomer in the reaction liquid to be 50 to 99% by mass (preferably 80 to 95% by mass).

[0115] The reaction conditions for the above reaction are not particularly limited. For example, the reaction temperature for the above reaction may be 60 to 100° C., or may be 70 to 90° C. The reaction time for the above reaction may be, for example, 0.5 to 5.0 hours, or may be 1.0 to 3.0 hours.

[0116] The present production method may further include a step of adding a silane oligomer to the reaction liquid after the modification step, thereby obtaining a composition containing the silane oligomer modified with the metal alkoxide and the unmodified silane oligomer.

[0117] The present manufacturing method may further include a step of adding a linear polysiloxane (and a silane monomer, if necessary) to the reaction liquid after the modification step. That is, the present manufacturing method may include a first step of preparing a silane oligomer at least partially modified with a metal alkoxide, and a second step of mixing the modified silane oligomer and the linear polysiloxane to obtain a barrier material-forming composition, and the first step may be the modification step. This results in the above-mentioned barrier material-forming composition.

[0118] The present production method may further include a step of adding other components to the reaction solution after the modification step. The present production method may further include a step of adding a liquid medium to the reaction solution after the modification step, or a step of replacing the liquid medium in the reaction solution after the modification step with another liquid medium. By these steps, various aspects of the above-mentioned composition can be prepared from the reaction solution after the modification step.

[0119] <Barrier material> The barrier material according to the present embodiment includes a polysiloxane compound doped with metal atoms. This barrier material may be a cured product of the above-mentioned barrier material-forming composition. This barrier material may also be formed by heating the above-mentioned barrier material-forming composition. The heating causes the silane oligomer, linear polysiloxane, and silane monomer in the composition to polymerize, forming a polysiloxane compound. At this time, since the silane oligomer is modified with a metal alkoxide, the formed polysiloxane compound is doped with metal atoms derived from the metal alkoxide.

[0120] The polysiloxane compound has a siloxane skeleton. In the polysiloxane compound, a metal atom is bonded to a silicon atom constituting the polysiloxane skeleton via an oxygen atom.

[0121] The silicon atoms contained in the polysiloxane compound can be classified into silicon atoms bonded to one oxygen atom (M unit), silicon atoms bonded to two oxygen atoms (D unit), silicon atoms bonded to three oxygen atoms (T unit), and silicon atoms bonded to four oxygen atoms (Q unit). Examples of the M unit, D unit, T unit, and Q unit are the above formulas (M), (D), (T), and (Q), respectively.

[0122] In the polysiloxane compound, the ratio of the total number of T units and Q units to the total number of silicon atoms is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. Such a polysiloxane compound further improves the moisture resistance of the barrier material. In addition, in the polysiloxane compound, the ratio of the total number of T units and Q units to the total number of silicon atoms may be, for example, 100% or less, or 95% or less.

[0123] In the polysiloxane compound, the molar ratio (M / Si) of metal atom M to the total number of silicon atoms (Si) may be, for example, 0.0001 or more, and is preferably 0.001 or more. This tends to improve curability. In addition, the molar ratio (M / Si) may be, for example, 0.5 or less, and is preferably 0.2 or less. This tends to improve transparency.

[0124] In the polysiloxane compound, it is preferable that most of the oxygen atoms are bonded to at least one silicon atom. The polysiloxane compound has a small amount of alcoholic hydroxyl groups (C-OH), ether bonds (COC), etc., and this tends to further improve moisture resistance. For example, it is preferable that 90% or more of the oxygen atoms in the polysiloxane compound are bonded to silicon atoms, preferably 95% or more are bonded to silicon atoms, and more preferably 99% or more are bonded to silicon atoms.

[0125] The barrier material has a low water vapor transmission rate and is excellent in moisture resistance. The water vapor transmission rate (40°C, 95% RH) of the barrier material per 25 μm thickness is, for example, 5000 g / m 2 ·day or less, 4000g / m 2 ·day or less is preferable, and 3000 / m 2 It is even more preferable that the temperature is 100°C or less.

[0126] The water vapor transmission rate (40°C, 95% RH) of the barrier material per 25 μm thickness is, for example, 100 g / m 2·day or more, 500g / m 2 Such a barrier material has moisture-wicking properties, and even when used in a high-temperature environment, it can sufficiently prevent damage caused by the expansion of moisture that has penetrated inside.

[0127] The water vapor permeability of the barrier material is a value measured by a moisture sensor method (Lyssy method) in accordance with JIS K7129.

[0128] The barrier material may be transparent. Such a barrier material can be suitably used in applications where transparency is required, such as a covering material for covering an image sensor in an image sensor package. Here, being transparent means that the visible light transmittance (light transmittance at 550 nm) per mm thickness is 80% or more.

[0129] The barrier material has a visible light transmittance (550 nm light transmittance) of preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more per mm of thickness. The visible light transmittance of the barrier material is measured by a spectrophotometer.

[0130] The barrier material has excellent insulating properties and can be suitably used in applications where insulating properties are required, for example, as a moisture-proof barrier material for electronic components.

[0131] The volume resistivity of the barrier material is, for example, 1×10 10 From the viewpoint of ensuring sufficient insulation as a moisture-proof barrier material for electronic components, the resistance is preferably 1×10 12 Ωcm or more is preferable, 1×10 14 The volume resistivity of the barrier material is preferably 1×10 19 It may be less than 1×10 18 In this specification, the volume resistivity of the barrier material is a value measured in accordance with JIS K 6911.

[0132] The dielectric breakdown strength of the barrier material may be, for example, 10 kV / mm or more, and from the viewpoint of ensuring sufficient insulation as a moisture-proof barrier material for electronic components, it is preferably 50 kV / mm or more, and more preferably 100 kV / mm or more. The dielectric breakdown strength of the barrier material may be, for example, 1000 kV / mm or less, or may be 500 kV / mm or less. In this specification, the volume resistivity of the barrier material indicates a value measured in accordance with JIS C 2110.

[0133] The barrier material has excellent heat resistance and can be suitably used in applications requiring heat resistance, such as a moisture-proof barrier material for electronic components that undergo a high-temperature process (e.g., a reflow process) during mounting. The barrier material can be suitably used, for example, as a moisture-proof barrier material that is placed on a component before heating in a reflow furnace and is subjected to the reflow furnace together with the component. Because the barrier material has excellent heat resistance, it can exhibit sufficient moisture resistance even after heating in a reflow furnace.

[0134] The 5% weight loss temperature (T d5 ) may be, for example, 260° C. or higher, preferably 280° C. or higher, and more preferably 300° C. or higher. The 5% weight loss temperature of the barrier material may be, for example, 500° C. or lower, or 450° C. or lower. In this specification, the 5% weight loss temperature of the barrier material indicates a value measured by a thermogravimetric differential thermal analyzer.

[0135] The shape of the barrier material is not particularly limited. The barrier material may be formed, for example, in a film shape, and such a barrier material can be used as a moisture-proof barrier film. The barrier material may be formed so as to fill a gap between members, and in this case, it is possible to prevent moisture from entering through the gap. The barrier material may be formed so as to cover a member, and in this case, it is possible to prevent the member from coming into contact with moisture.

[0136] <Method of manufacturing barrier material> The method for producing a barrier material according to the present embodiment includes a heating step of heating the above-mentioned composition to form a barrier material. In this method, the silane oligomer and linear polysiloxane (and optionally silane monomer) in the composition are polymerized by heating to form a polysiloxane compound. At this time, since at least a portion of the silane oligomer in the composition is modified with a metal alkoxide, the polysiloxane compound is doped with metal atoms derived from the metal alkoxide.

[0137] In the heating step, the liquid medium in the composition may be removed by heating, i.e., the heating step may be a step of forming a barrier material containing a polysiloxane compound by drying the composition by heating.

[0138] The heating temperature in the heating step is not particularly limited, and may be any temperature at which the silane oligomer can be polymerized. In addition, when the composition contains a liquid medium, the heating temperature is preferably a temperature at which the liquid medium volatilizes. The heating temperature may be, for example, 70°C or higher, and preferably 100°C or higher. In addition, the heating temperature may be, for example, 200°C or lower, and preferably 180°C or lower.

[0139] The present manufacturing method may further include a coating step of coating the composition. In this case, the heating step can be said to be a step of heating the coated composition.

[0140] The method for applying the composition is not particularly limited, and may be appropriately changed depending on the shape of the object to be applied, the thickness of the barrier material, etc.

[0141] In the method, the composition may be applied to an object to which moisture resistance is to be imparted, thereby forming a barrier material on the object. Alternatively, the method may involve producing a barrier material of a predetermined shape, and then applying the produced barrier material onto the object.

[0142] <Barrier material applications> The use of the barrier material according to the present embodiment is not particularly limited, and the barrier material can be suitably used in various applications requiring moisture resistance. For example, the barrier material can be suitably used as a moisture-proof barrier material for electronic components.

[0143] The barrier material according to this embodiment has excellent moisture-proof properties even in a high-temperature environment (for example, 100° C. or higher). Therefore, the barrier material according to this embodiment can be suitably used for applications such as a moisture-proof barrier material for electronic components used in a high-temperature environment and a moisture-proof barrier material for electronic components that undergo a high-temperature process during mounting. Specifically, the barrier material according to this embodiment can be suitably used as a moisture-proof barrier material for power semiconductors, a moisture-proof barrier material for image sensors, a moisture-proof barrier material for displays, and the like.

[0144] A preferred embodiment of the application of the barrier material will be described in detail below, but the application of the barrier material is not limited to the following.

[0145] <Application example 1> One embodiment of the present invention relates to a product having a moisture-proof treated member. Such a product includes a member and a barrier material formed on the member. The barrier material may be formed on one member or on multiple members. The barrier material may be formed to cover one or multiple members, or may be formed to cover a joint between two members, for example.

[0146] Such a product is produced by a manufacturing method including a first step of applying the above-mentioned barrier material-forming composition onto a member and a second step of heating the applied composition to form a barrier material on the member. This manufacturing method may further include a step of exposing the moisture-proofed member to high temperatures (e.g., reflow soldering, thermal curing of chip bonds, drying of materials by heating, etc.).

[0147] Specific examples of such applications include the following electronic components:

[0148] (Electronic parts A-1) An electronic component in one embodiment includes a substrate, a cover glass, an image sensor disposed between the substrate and the cover glass, a support member that supports the cover glass and the image sensor on the substrate, and the above-mentioned barrier material provided on the joint between the cover glass and the support member.

[0149] Such electronic components can be manufactured, for example, by a manufacturing method including a coating step of applying a barrier material-forming composition to the joint between the support member and the cover glass, and a barrier material-forming step of heating the applied composition to form a barrier material on the joint.

[0150] (Electronic Part A-2) An electronic component according to one embodiment includes a substrate, an image sensor disposed on the substrate, and the barrier material provided on the image sensor.

[0151] The barrier material can be excellent in moisture resistance and transparency. Therefore, the barrier material can be suitably used as a sealing material for sealing an image sensor. Since such an electronic component can form an image sensor package without using a cover glass, it is expected that the component size can be reduced and the handling can be improved.

[0152] In this application, the visible light transmittance (550 nm) of the barrier material per mm thickness is preferably 95% or more, more preferably 97% or more, and even more preferably 99% or more.

[0153] Such electronic components can be manufactured, for example, by a manufacturing method including a coating step of coating a barrier material-forming composition onto an image sensor, and a barrier material-forming step of heating the applied composition to form a barrier material on the image sensor.

[0154] <Application example 2> One embodiment of the present invention relates to a product having a first member and a second member joined to the first member, and a joint between the first member and the second member is moisture-proofed. Such a product includes the first member, the second member, and a barrier material provided between the first member and the second member, and the first member and the second member are joined via the barrier material.

[0155] Such a product can be produced by a manufacturing method including a first step of disposing a barrier material-forming composition between a first member and a second member, and a second step of heating the composition to form a barrier material and bonding the first member and the second member via the barrier material. This manufacturing method may further include a step of exposing the first member and the second member bonded via the barrier material to high temperatures (e.g., reflow soldering, thermal curing treatment of chip bond, drying material by heating, etc.).

[0156] Specific examples of such applications include the following electronic components:

[0157] (Electronic parts B-1) An electronic component in one embodiment includes a substrate, a cover glass, an image sensor disposed between the substrate and the cover glass, a support member that supports the cover glass and the image sensor on the substrate, and a barrier material that bonds the cover glass and the support member.

[0158] Such electronic components can be manufactured, for example, by a manufacturing method including the steps of placing a barrier material-forming composition between a support member and a cover glass, heating the composition to form a barrier material, and bonding the support member and the cover glass via the barrier material.

[0159] <Application example 3> One embodiment of the invention relates to a product including a moisture barrier member. Such a product may be, for example, an assembly of multiple components including the moisture barrier member, the moisture barrier member being made of a barrier material.

[0160] Such a product can be produced by a manufacturing method including a first step of heating the barrier material-forming composition to produce a moisture-proof member made of a barrier material, and a second step of assembling a plurality of members including the moisture-proof member. This manufacturing method may further include a step of exposing the assembly obtained in the second step to high temperatures (e.g., reflow soldering, thermal curing treatment of chip bonds, drying materials by heating, etc.).

[0161] Specific examples of such applications include the following electronic components:

[0162] (Electronic parts C-1) An electronic component according to one embodiment includes a substrate, at least one component selected from the group consisting of a MEMS sensor, a wireless module, and a camera module, and a moisture-proof member having a barrier material.

[0163] The barrier material has excellent moisture resistance, and therefore the electronic component has excellent moisture resistance, and degradation of the sensing characteristics due to moisture absorption is sufficiently prevented.

[0164] Such electronic components can be manufactured, for example, by a manufacturing method including a step of preparing a moisture-proof member having a barrier material by heating a barrier material-forming composition, and a step of assembling a plurality of components including the moisture-proof member. Here, the barrier material may be formed independently of the substrate and the component, or may be formed integrally with the component by heating the barrier material-forming composition applied onto the component.

[0165] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0166] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0167] Example 1 [Barrier material forming composition A-1] 3.8 parts by mass of aluminum sec-butoxide (manufactured by Matsumoto Fine Chemical Co., Ltd., product name: AL-3001, hereinafter abbreviated as "AL-3001"), 7.6 parts by mass of tert-butyl alcohol (manufactured by Wako Pure Chemical Industries, Ltd.), 0.3 parts by mass of water, 0.3 parts by mass of acetic acid, and 64.9 parts by mass of silane oligomer (manufactured by Shin-Etsu Chemical Co., Ltd., product name: X-40-9227) were mixed and reacted at 70°C for 1 hour. Next, 23.4 parts by mass of methyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM-13, hereinafter abbreviated as "MTMS"), 2 parts by mass of 3-aminopropyltriethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-903), and linear polysiloxane (manufactured by Momentive Performance Materials Japan, LLC, product name: YF3800, kinetic viscosity at 25 °C: 80 mm 2 / s) was mixed to obtain a barrier material forming composition A-1.

[0168] [Evaluation board A-1 with barrier material] One side of a 0.4 mm thick copper-clad laminate MCL-E-700G (product name, manufactured by Hitachi Chemical Co., Ltd.) was masked, and the copper foil on one side was removed by immersion in a copper etching solution to produce a 40 mm square base substrate. Next, a barrier material forming composition 1 was applied to the surface of the base substrate from which the copper foil had been removed so that the thickness after drying would be 30 μm, and the substrate was dried at 150° C. for 4 hours. As a result, a barrier material was formed on the substrate, and an evaluation substrate A-1 with a barrier material was obtained. The 5% weight loss temperature of the obtained barrier material was 308° C., and the resistivity of the barrier material was 1.4×10 15 It was Ωcm.

[0169] [Evaluation method] The barrier material-forming composition A-1 and the evaluation substrate A-1 with a barrier material were evaluated for transparency, moisture absorption rate (%), and the presence or absence of cracks by the following methods. <Transparency evaluation> The barrier material-forming composition A-1 was visually observed and rated as A when it was transparent and no cloudiness was observed, and as B when cloudiness was observed. <Evaluation of moisture absorption rate> The evaluation substrate with the barrier material was dried at 130°C for 1 hour using a safety oven (manufactured by Espec Corporation, product name: SPHH-202) to obtain a measurement sample. The mass of the obtained measurement sample was measured to determine the initial mass m1. Next, a temperature and humidity chamber (manufactured by Kato Corporation, product name: SE-44CI-A) was used to treat the sample in an atmosphere of 85°C / 85% RH for 100 hours to obtain a sample after constant temperature and humidity treatment. The mass of the measurement sample after constant temperature and humidity treatment was measured to determine the mass after constant temperature and humidity treatment m2. The moisture absorption rate Q was calculated from the initial mass m1 and the mass after constant temperature and humidity treatment m2 according to the following formula: A (%) was calculated. Q A =100×(m1-m2) / m2 <Cracks present or absent> The evaluation substrates with the barrier material were visually observed, and rated as A if there were no cracks in the barrier material, and B if there were cracks.

[0170] [Heat resistance confirmation test] A 10 cm x 10 cm polyimide film (thickness 125 μm, Toray DuPont Co., Ltd., product name: Kapton (registered trademark) 500H / V) was dip-coated with the barrier material forming composition A-1 and dried at 150°C for 4 hours to form a barrier material with a thickness of 20 μm, and a measurement sample was obtained. The mass of the obtained measurement sample was measured to determine the initial mass m3. Next, a constant temperature and humidity chamber (manufactured by Kato Co., Ltd., product name: SE-44CI-A) was used to treat the sample in an atmosphere of 85°C / 85% RH for 168 hours to obtain a sample after constant temperature and humidity treatment. The mass of the measurement sample after constant temperature and humidity treatment was measured to determine the mass after constant temperature and humidity treatment m4. From the initial mass m3 and the mass after constant temperature and humidity treatment m4, the moisture absorption rate Q was calculated according to the following formula: B1 (%) was calculated. Q B1 =100×(m3-m4) / m4 Next, the measurement sample prepared in the same manner as above was heated to 260°C to simulate the reflow process. The measurement sample after heating was subjected to the same constant temperature and humidity treatment as above. The moisture absorption rate Q was calculated from the initial mass m5 before the constant temperature and humidity treatment and the mass m6 after the constant temperature and humidity treatment using the following formula: B2 (%) was calculated. Q B2 =100×(m5-m6) / m6 Moisture absorption rate Q B1 is 1.1%, moisture absorption rate Q B2 The moisture absorption rate was 1.2%, and it was confirmed that the high moisture absorption rate could be maintained even after the solder was exposed to high temperatures in the reflow process and other processes.

[0171] Example 2 Instead of YF3800 as the linear polysiloxane, YF3804 (product name, manufactured by Momentive Performance Materials Japan, LLC, kinematic viscosity at 25°C: 80 mm 2 A barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1, except that a fluorine-containing ...

[0172] Example 3 Instead of YF3800 as a linear polysiloxane, XF3905 (product name, manufactured by Momentive Performance Materials Japan, LLC, kinematic viscosity at 25°C: 700mm 2 A barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1, except that a fluorine-containing ...

[0173] Example 4 Instead of YF3800 as a linear polysiloxane, XF3057 (product name, manufactured by Momentive Performance Materials Japan, LLC, kinematic viscosity at 25°C: 3000mm 2 A barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1, except that a fluorine-containing ...

[0174] Example 5 Except for changing the amount of linear polysiloxane added to 10 parts by mass, a barrier material-forming composition and a substrate for evaluation with a barrier material were obtained in the same manner as in Example 1. The obtained barrier material-forming composition and substrate for evaluation with a barrier material were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0175] Example 6 Except for changing the amount of linear polysiloxane added to 15 parts by mass, a barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1. The obtained barrier material-forming composition and evaluation substrate with a barrier material were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0176] Comparative Example 1 Instead of YF3800 as a linear polysiloxane, XC96-723 (product name, manufactured by Momentive Performance Materials Japan, LLC, kinematic viscosity at 25°C: 30 mm 2 A barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1, except that a fluorine-containing ...

[0177] Comparative Example 2 Instead of YF3800 as the linear polysiloxane, KBM-3066 (product name: Shin-Etsu Chemical Co., Ltd., kinematic viscosity at 25°C: 3.5 mm 2 A barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1, except that a fluorine-containing ...

[0178] Comparative Example 3 Except for not adding the linear polysiloxane, a barrier material-forming composition and an evaluation substrate with a barrier material were obtained in the same manner as in Example 1. The obtained barrier material-forming composition and the evaluation substrate with a barrier material were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0179] [Table 1]

[0180] As shown in Table 1, barrier materials having high moisture absorption rate and no cracks were formed in Examples 1 to 6. Moreover, barrier materials having high moisture absorption rate, no cracks, and excellent transparency were formed in Examples 1, 2, 5, and 6. On the other hand, cracks were observed in the barrier materials in Comparative Examples 1 to 3, and the moisture absorption rate was lower than that of the Examples.

Claims

1. A first step of preparing a modified silane oligomer by modifying a silane oligomer with 0.001 to 30 parts by mass of a metal alkoxide relative to 100 parts by mass of the silane oligomer; The silane oligomer and a kinetic viscosity of 50 mm at 25° C. 2 a second step of obtaining a barrier material-forming composition by mixing a linear polysiloxane having a viscosity of from 1000 mm 2 / s to 3000 mm 2 / s, a first silane monomer represented by the following formula (A-1), and a second silane monomer which is an alkyltrialkoxysilane; Equipped with In the silane oligomer, the ratio of the total number of T units represented by the following formula (T) and Q units represented by the following formula (Q) to the total number of silicon atoms is 50% or more: The linear polysiloxane has a polysiloxane chain constituted by repeating D units represented by the following formula (D) as a main chain, the linear polysiloxane has silanol groups at both ends, the content of the linear polysiloxane in the barrier material-forming composition is 0.1 parts by mass or more and 40 parts by mass or less based on 100 parts by mass of the silane oligomer, the content of the first silane monomer in the barrier material-forming composition is 0.01 parts by mass or more and 5 parts by mass or less based on 100 parts by mass of the silane oligomer, The content of the second silane monomer in the barrier material-forming composition is 5 parts by mass or more and 40 parts by mass or less based on 100 parts by mass of the silane oligomer. A method for producing a barrier material-forming composition. 【Chemistry 1】 [In the formula, R represents an alkyl group or an aryl group.] 【Chemistry 2】 [In the formula, R A1 represents an amino group, L 1 represents an alkanediyl group or an oxyalkanediyl group, p represents an integer of 1 or more, and RA2 represents an alkyl group or an aryl group.

2. Said L 1 is an alkanediyl group having 2 to 8 carbon atoms, said p is 1, The method according to claim 1, wherein the alkyltrialkoxysilane is a silane compound in which one alkyl group having 6 or less carbon atoms and three alkoxy groups are bonded to a silicon atom.

3. The method according to claim 1 or 2, wherein the first step comprises reacting the silane oligomer with the metal alkoxide to obtain the modified silane oligomer.

4. The method according to claim 1 or 2, wherein the first step comprises reacting a silane monomer with a metal alkoxide to obtain the modified silane oligomer.

5. A method for manufacturing a barrier material, comprising a step of hardening a barrier material-forming composition manufactured by the manufacturing method described in claim 1 or 2 to form a barrier material.

6. A method for manufacturing a product having a moisture-proof treated member, comprising the steps of: A first step of applying a barrier material-forming composition produced by the method according to claim 1 or 2 onto a member; a second step of curing the applied composition to form a barrier material on the member; A manufacturing method comprising:

7. A method for manufacturing a product having a first member and a second member joined to the first member, the joint between the first member and the second member being subjected to a moisture-proofing treatment, comprising: A first step of disposing a barrier material forming composition produced by the method according to claim 1 or 2 between a first member and a second member; a second step of curing the composition to form a barrier material and bonding the first member and the second member via the barrier material; A manufacturing method comprising:

8. A method for manufacturing a product including a moisture-proof member, comprising: A first step of producing a moisture-proof member having a barrier material by curing the barrier material-forming composition produced by the production method according to claim 1 or 2; a second step of assembling a plurality of members including the moisture-proof member; A manufacturing method comprising:

Citation Information

Patent Citations

  • Curable organopolysilixane composition

    JP1997296115A

  • Organic-inorganic hybrid composition

    JP2008231402A

  • Thermosetting composition and optical semiconductor device

    JP2010065166A

  • Barrier film laminate

    JP2011093195A

  • Sealing material for LED

    JP2013049834A